Characterization and thermal dehydration kinetics of admontite mineral hydrothermally synthesized from magnesium oxide and boric acid precursor - Derun, Emek Moroydor; Kipcak, Azmi Seyhun; Senberber, Fatma Tugce; Yilmaz, Muge Sari (SPRINGER, 2015)
Magnesium borates are one of the major groups of boron minerals that have high heat and corrosion resistance and high coefficients of elasticity. In this study, magnesium borate minerals are hydrothermally synthesised using boric acid and magnesium oxide and are characterised by various analysis techniques. A drying temperature of 40 A degrees C was used. From the results obtained, admontite mineral is synthesised purely at a reaction temperature of 100 A degrees C and reaction times of both 120 and 240 min. Characterisations of the products are determined with the techniques of X-ray diffraction, Fourier transform infrared spectroscopy, Raman spectroscopy, scanning electron microscopy, differential thermal analysis and thermal gravimetry analysis. Additionally, overall admontite yields were calculated and varied between 89.98 +/- A 3.05 and 89.07 +/- A 1.28 %. Moreover, a kinetic study using the Ozawa, Kissenger, and Doyle methods was performed in the stage of decomposition of admontite that had been synthesised at a reaction time of 240 min.
Keywords: Magnesium borate hydrate; Hydrothermal synthesis; Reaction yield; Dehydration kinetics; Chemistry